Mite Domatia and Associated Mite Density in a North American Eastern Deciduous Forest in Michigan - Carolyn D. K. Graham; Lillian R. Bailey; Ashley E. Cole; Anna M. Cress; Emma Dawson‐Glass; Bailee D. Duke; Liam J. Estill; Lauren D. Jones; Gabrielle R. Leon; Samantha Molino; Nia G. Paton; Abrianna J. Soule; et al. (Ecology and Evolution)
ABSTRACT Mite–plant defense mutualisms are among the most common defense mutualisms in the world—yet studies providing basic information on their prevalence in plant communities remain rare. Here, we systematically surveyed common woody plants in a North American deciduous forest for the presence of plant–mite mutualistic interactions. We scored 16 common woody species in a wooded natural area for the presence and number of mite domatia—small structures on the underside of plant leaves that are known to house mutualistic mites. We found that 80% of common woody species in the forest had mite domatia, the highest reported percentage of mite domatia in any survey conducted thus far. We paired our survey with a quantification of the number of mites found on each leaf and investigated the relationship between mite domatia and mite abundance within and across species. We found that plants with mite domatia had significantly more mites on their leaves than species that lacked mite domatia, and that plants with more domatia had more mites. Together, our study provides much needed systematic survey data on plant–mite mutualism prevalence in an important plant community and points to northern temperate forests as a promising system to study plant–mite mutualisms in high densities in the future.